Efektivitas Psikoedukasi Tentang Masalah Kesehatan Jiwa Terhadap Penerimaan Keluarga Pasien Pasca Perawatan Skizofrenia di Puskesmas Karang Asam Samarinda - Angriani, olivia; Safrudin, Muhammad Bachtiar (LPPM Universitas Sari Mulia, 2024)
Background: Schizophrenia is a mental disorder that causes mental disorders in sufferers both mentally, in terms of thought patterns and emotionally. The problem of schizophrenia treatment causes sufferers to need help from others, especially family. The family is involved in the treatment so that the family must accept the patient well in supporting treatment and care. Treatment actions that are attempted to increase family acceptance are carried out through psychoeducation. Objective: To determine the effect of psychoeducation about mental health on the acceptance of families of patients after schizophrenia treatment at the Karang Asam Samarinda Health Center. Method: Quantitative research type with a Quasy Experimental one group pre and posttest without control group Design. The total sampling technique is 40 families as caregivers of schizophrenia patients in the Karang Asam Health Center work area. Result: Psychoeducational interventions will be carried out in 4 sessions in 1 week. Data collection uses a questionnaire that has been tested valid and reliable. Research results: the results of data analysis obtained a mean pre value of 83.19 and a mean post value of 113.15, while the difference in mean pre-intervention and post-intervention after 1 month was 29.81. The results of the Paired t-test obtained a p-value of 0.000 <α (sig <0.05). Conclusion: there is an effect of Psychoeducation About Mental Health Problems on Family Acceptance of Post-Schizophrenia Treatment Patients at the Karang Asam Samarinda Health Center